The diaphragm coupling in energy equipment: A review - Wang, Guoping; Liu, Jixuan; Cheng, Shuang; Yan, Feifei; Jia, Qian; Han, Haiyan (Frontiers in Energy Research, 2022)
With the rapid development of high-speed rotating machinery, diaphragm couplings are widely used in energy equipment such as compressors, generators, drilling equipment, and turbine drives by virtue of their high sensitivity, oil resistance and corrosion resistance. However, the theoretical research of this product mainly focuses on the design of diaphragm profile, the combination form between diaphragms, the overall structural form of diaphragm coupling and the axial dynamic characteristics of diaphragm coupling. Therefore, this paper analyzes and summarizes the current research status of diaphragm couplings in the world, and puts forward the problems that need to be solved in the field of diaphragm coupling research, and proposes a new direction for the subsequent research.